2022
DOI: 10.2991/assehr.k.220110.177
|View full text |Cite
|
Sign up to set email alerts
|

From the Perspective of Social Media

Abstract: The study sets up a research question that whether comments on social media affect their perceptions of Lesbian Gay Bisexual Transgender (LGBT) group. It was a gap and there were no people to investigate this question in the past. Also, the study used Chinese social media, Weibo, to collect the comments of the LGBT group. And then, the study sets up a questionnaire interview to get data from different people. After that, the data was analysed by some charts and SWOT. These charts explored the relationship betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Our research found that Tanbi product consumption online facilitates adolescents' early understanding and awareness of same-sex attraction. Unlike hidden gay topics in mainstream mass media, the flourishing of Internet Tanbi drama, which talks about the culture of Boy's Love (BL) and popular among sexual minority as well as heterosexual adolescents creates a chance for sexual minority culture to officially go into the public view ( 30 ). Pan's research pointed out that Tanbi products potentially impacted on Chinese adolescents' sexual orientation.…”
Section: Discussionmentioning
confidence: 99%
“…Our research found that Tanbi product consumption online facilitates adolescents' early understanding and awareness of same-sex attraction. Unlike hidden gay topics in mainstream mass media, the flourishing of Internet Tanbi drama, which talks about the culture of Boy's Love (BL) and popular among sexual minority as well as heterosexual adolescents creates a chance for sexual minority culture to officially go into the public view ( 30 ). Pan's research pointed out that Tanbi products potentially impacted on Chinese adolescents' sexual orientation.…”
Section: Discussionmentioning
confidence: 99%
“…The desire to express oneself on social media lights up the same part of the brain that activates while taking some addictive element. 1 It is also found that there is an irrefutable connection between the usage of social media, bad physical and mental health, and low self-esteem, which has become more severe due to the pandemic. 2 Another study from California State University reported that in Bangladesh there were 45 million (27.2% of the total population) social media users in January 2021 and the number increased by 9 million (25%) between 2020 and 2021.…”
Section: Introductionmentioning
confidence: 99%